Empowerment of the Students Creativity Through Participatory Art Project in Surakarta - Adam Wahida (IJCAS (International Journal of Creative and Arts Studies), 2015)
The general objective of the participatory art project creation is to provide inspiration and concrete solutions to the creativity problems of senior high school students in Surakarta. While specifically aims to: 1) create useful the art strategies to empower the students creativity, 2) realize the art project that favors the development of students creativity potential, 3) create many artwork that comes from the students socio-cultural context. The methods of participatory art creation were done by: 1) an intensive on-site art project that was on going at SMAN 5 Surakarta, SMA Murni and MA Al-Islam in Surakarta. Object observation included student activities in and outside of school, the learning atmosphere in the classroom, student work documents, and documents teacher (curriculum, syllabus, lesson plans, learning materials). 2) In-deep interviews; with the head master, teachers, and students. 3) The literature review; to examine the theory to reinforce the concepts as a foundation that provides clear direction and path in the process of creating art works for the purpose of creating some participatory artwork. 4) Workshop and experiments; provide workshops of art creation to the students and conduct experiments with materials, techniques and formats in order to achieve a shape that corresponds to the concept of creation. The results of this art project are: 1) the product of participatory art creation strategies that are able to empower the students creativity. 2) the realization of participatory art project moving in the area of art creativity empowerment of students in the school. 3) the creation of art works based on the socio-cultural context, namely: print making, comic strips, comic puppets, etching. Through the creation of a participatory art project has been a change as follows: 1) An increase in the students activity receiving learning material of art creation, especially of the creativity led to the idea in visual forms. 2) Participatory art project can be oriented to direct experience of completing a variety of problems from simple. 3) The students have a skills to creative thinking with a different perspective and can be flexibly applied to solve a of problems as well welcoming the opportunity.